Differences in throwing kinematics due to changes in run-up speed in javelin throwing - Makino, M.; Nakayama, K.; Ando, Y.; Tauchi, K. (The Journal of Sports Medicine and Physical Fitness, 2025)
BACKGROUND: In javelin throw training, although short run-up throwing is more frequently performed than full run-up throwing (throwing like a competition), it is unclear whether the throwing motion of the short run-up throwing is different from full run-up throwing. Therefore, the purpose of this study was to clarify the differences between the short and full run-up throwing in javelin throw. METHODS: Twelve male javelin throwers were included in this study. The participants performed one-cross throwing (Cross), which involved throwing from a short run-up, and full run-up throwing (Run), which was similar to a competition. The coordinates of the reflective markers attached to the participant`s body and javelin was recorded using an optical motion capture system. The analysis phase was from the time of last foot contact to the time of release. We calculated the kinematic variables related to javelin throwing performance and compared the Cross and Run. RESULTS: The results showed significant differences in the joint angles of the left knee, trunk, and right shoulder between Cross and Run. CONCLUSIONS: The results indicate that different throwing motions occur in short run-up throwing compared to full run-up throwing.